Implementasi Smart Building IoT Identifikasi Wajah, Sensor Pir, dan Sensor Gas Untuk Keamanan Showroom - Andika Alhaetami; R Tommy Gumelar; Shevti Arbekti Arman (ITB Ahmad Dahlan Jakarta, 2026)
Security and energy efficiency are crucial aspects of a car showroom that can be improved using an IoT-based smart building system. This research develops a system integrating a PIR sensor for automatic lighting, an MQ2 sensor for gas detection, and an ESP32-CAM for facial recognition to enhance security. The ESP32 microcontroller controls the system, enabling real-time monitoring via the Telegram application. Testing results show that the PIR sensor optimizes energy use by activating lights only when motion is detected. The MQ2 sensor provides early warnings for hazardous gases, while the ESP32-CAM ensures restricted access by identifying authorized personnel. IoT integration allows stable data transmission and remote control. This system effectively enhances showroom security and energy efficiency, offering fast response times and reliable performance. The findings provide a foundation for further smart building innovations applicable to various industries.